2004
DOI: 10.1081/al-120039437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Syringe‐Connected Minicolumn Technique for Preconcentration of Some Trace Elements Using Chromosorb‐103 and Determination by Flame Atomic Absorption Spectrometry

Abstract: A syringe-connected minicolumn (SCM) technique has been developed for preconcentration and enrichment of cobalt, iron, and lead in riverwater samples prior to their determination by flame atomic absorption spectrometry (FAAS). The proposed technique is substituted for the 1-5%). The developed technique is simple, fast, and accurate. Detection limits (3s) were 4.8 mg L 21 for Co, 14 mg L 21 for Fe, and 15 mg L 21 for Pb. Very high preconcentration factors up to 200-fold could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Solid phase extraction based on the adsorption is also one of the important preconcentration methodologies [8][9][10][11][12][13][14][15]. It has some advantages including short analysis time, high preconcentration factors, low consumption of the organic solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid phase extraction based on the adsorption is also one of the important preconcentration methodologies [8][9][10][11][12][13][14][15]. It has some advantages including short analysis time, high preconcentration factors, low consumption of the organic solvent.…”
Section: Introductionmentioning
confidence: 99%
“…It has some advantages including short analysis time, high preconcentration factors, low consumption of the organic solvent. In the solid phase extraction of the metal ions various adsorbents such as Amberlite resins [8,[10][11][12][13][14] molten naphthalene [15] chromos orb resins [16,17] activated carbons [18][19][20] silica gel [21][22][23][24] were employed for the separation and preconcentration of the metal ion in the various environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…Several analytical techniques, including atomic absorption spectrometry (Pourreza and Ghanemi 2006;Taher et al 2005;Bakireioglu et al 2004), inductively coupled plasma-atomic emission spectrometry (Guo et al 2004;Liu et al 2005), voltammetry (Kumar et al 2005), and spectrophotometry (Pinto et al 2002;Isıldak et al 1999;Jankiewicz et al 1999;Prodromidis et al 1994) have been reported for the determination of copper in various samples. However, spectrophotometric methods are often preferred, as they involve inexpensive instrument and provide high sensitivity with an appropriate chromogenic reagents.…”
mentioning
confidence: 99%
“…This procedure was handy, fast and convenient. [6][7][8][9][10][11][12][13] The amine groups are one of the most efficient functional groups for the removal of heavy metal ions, 14,15 and various adsorbents with amine functional groups have been developed from natural biopolymers, e.g. chitosan, which contains amine groups in its backbone, 16 or from synthetic polymers that are subsequently immobilized with the amine groups.…”
Section: Introductionmentioning
confidence: 99%